Comparison Between Continuous and Interrupted Fascial Closure in Emergency Midline Laparotomy - Shahab, Fatima (Indus Journal of Bioscience Research, 2025)
Objective: To compare the effectiveness of interrupted versus continuous fascial closure techniques in emergency midline laparotomy in terms of the frequency of burst abdomen. Study Setting: Department of Surgery, DHQ Hospital, Faisalabad. Duration of Study: July 31, 2024 to January 31, 2025 (Six months following approval of the synopsis) Data Collection: A randomized controlled trial was conducted on 150 patients undergoing emergency midline laparotomy. Patients were randomly assigned to either interrupted (n=75) or continuous (n=75) closure techniques. The primary outcome was burst abdomen, assessed over a 30-day postoperative period. Results: The incidence of burst abdomen was significantly lower in the interrupted closure group (4 cases, 20.0%) compared to the continuous closure group (16 cases, 80.0%) (p = 0.004). Stratified analysis showed that the continuous closure technique was associated with a significantly higher risk of burst abdomen across different age groups, gender, and BMI categories. However, there was no significant difference in superficial surgical site infections between the two groups (p = 0.273). Conclusion: Interrupted fascial closure significantly reduces the incidence of burst abdomen in emergency midline laparotomy compared to continuous closure. Given its effectiveness in preventing wound dehiscence, interrupted closure should be preferred in emergency settings. Further multicenter trials with extended follow-up periods are warranted to confirm long-term outcomes.